PENGARUH COATING ALGINATE-CHITOSAN TERHADAP PERTUMBUHAN MIKROBA PADA BUAH MELON KUPASAN - Heru Cahyana; Marcelinus Christwardana; Nur Rokhati (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2012)
Lack of peeling fruit processing now cause the rapid spoilage the fruit. Therefore, most of the industry slows microbial growth by using a coating on the fruit. In this study making edible films made from alginate and chitosan. Edible film also applied to peeling melon and tested the microbial growth during 3 days. The result showed melon which coating with chitosan film is very good because this film can hold up during 2 days with growth of microbe to 21,6 x 105 CFU/gr.